2020
DOI: 10.1038/s41598-020-57926-7
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of anterior segment measurements by optical coherence tomography combined with Placido disk corneal topography in eyes with keratoconus

Abstract: corneal tomography is an important tool to identify and follow up eyes with keratoconus. our study evaluate the repeatability of the automatic measurements provided in keratoconic eyes by a new anterior-segment optical coherence tomographer (AS-oct) combined with placido-disk topography (MS-39, CSO) and assess their agreement with the corresponding measurements taken with a rotating Scheimpflug camera combined with Placido-disk topography (Sirius, CSO). Mean simulated keratometry, posterior and total corneal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 26 publications
(22 reference statements)
4
41
0
1
Order By: Relevance
“…MS-39 uses Spectral-domain OCT (SD-OCT) and Placido Disk corneal topography to obtain measurements from the anterior segment of the eye. The repeatability of corneal sub-layer measurements performed with this device in healthy eyes and corneas affected by keratoconus was previously reported 19,20 .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…MS-39 uses Spectral-domain OCT (SD-OCT) and Placido Disk corneal topography to obtain measurements from the anterior segment of the eye. The repeatability of corneal sub-layer measurements performed with this device in healthy eyes and corneas affected by keratoconus was previously reported 19,20 .…”
Section: Discussionmentioning
confidence: 60%
“…Studies using high-resolution AS-OCT confirmed these findings and were used to create a classification for the severity of keratoconus 27,28 . Anterior segment OCT combined with Placido topography (MS-39) used in this study was previously validated in normal eyes, keratoconic corneas, and eyes following excimer laser treatment 19,20 . In this study, high-resolution AS-OCT cross-sections allowed the identification of intrastromal lenticule profiles and the assessment of changes in the corneal epithelial and stromal regional thickness over time.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of OCT with SLB conducted by both Stehouwer et al [41] and Mueller et al [42] can image both anterior and posterior segments more efficiently but only provides structural images. Other groups have applied the combinations of OCT [43,44] or a Scheimpflug camera [45] and corneal topography with a focus only on the anterior segment biometry measurements. Compared with current ophthalmic imaging modalities, our self-developed multi-modal anterior eye imager not only offers precise structural information with the UHR-OCT module, but also provides functional information of bulbar conjunctival vessels through the microvascular imaging module.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-modal systems will not only improve the examination efficiency by reducing patients' moving from one examination system to the others, but also reduce the space and equipment investment. To date, researchers have developed a variety of multi-modal systems to combine the merits of each imaging modality for human eye imaging [36][37][38][39][40][41][42][43][44][45], among which, however, most are focused on posterior segment imaging [36][37][38][39][40]. Hybrid systems for anterior human eye imaging are relatively rare: few researches have demonstrated the integration of OCT system into SLB for both anterior and posterior segment imaging to improve the examination efficiency [41,42]; multi-modal systems combining OCT and corneal topography have been developed for anterior segment biometry measurements and applied to eyes with keratoconus [43,44]; a Scheimpflug camera combined with corneal topography has been used to measure pre/post-refractive surgery eyes [45].…”
mentioning
confidence: 99%
“…First, the mean or median value of multiple measurements could be used. Second, anterior-segment OCT could be used instead of traditional corneal tomography; the higher resolution, higher definition, and relatively higher quality of anterior segment scans may produce better results [ 35 ]. Third, Placido-disk, Scheimpflug, and anterior-segment OCT protocols could all be used to measure the corneal curvature, but each has its advantages [ 36 ].…”
Section: Discussionmentioning
confidence: 99%